Institutional choice vs communication in social dilemmas – an experimental approach - Ivo Bischoff (Justus-Liebig-Universität Gießen, Fachbereich Wirtschaftswissenschaften, 2006)
This paper presents an experimental study that compares the ability of human groups to escape the tragedy of the commons through institutional change or communication. Teams of five players are placed in a dynamic CPR environment with inefficient institutional settings. The results clearly show the vital importance of communication. At the same time, the groups who were allowed to replace the inefficient institutional settings by other more appropriate rules performed worse than those groups who were not given this opportunity.
Keywords: Q20; D62; D71; C92; 330; social dilemmas; laboratory experiment; group behavior; institutional choice; communication; Gefangenendilemma; Allmenderessource; Institutioneller Wandel; Gruppenentscheidung; Experiment; Theorie